Analysis of The Effect of Shopping Life Style and Fashion Involvement on Impulse Buying Behavior on Morningclo Thrift Store Consumers - Khansa, Teta Cyndia (International Journal of Review Management Business and Entrepreneurship (RMBE), 2022)
The purpose of this research is to find out the effect of shopping lifestyle and fashion involvement on the impulse buying behavior of Morningclo Thrift Store consumers. The method used is quantitative research. The population used in this study were 85 Morningclo consumer employees. The data technique in this study was carried out by distributing questionnaires using a Likert scale. Based on the results of data analysis, it can be denied that the shopping lifestyle (X1) has a significance value of 0.000<0.05 . So it can be said that H1 is accepted which means that the shopping lifestyle has a significant effect on impulsive buying behavior at Morningclo Thrift Store and the fashion engagement variable (X2) has asignificance value of 0.000<0.05. So it can be said that H2 is accepted which means that the price has a significant effect on impulsive buying behavior at the Morningclo Thrift Store.